Decision-Making at the Top - Borsting, Jack R. (Management Science, 1982)
The author's current decision-making environment is summarized. A short history of the Planning, Programming and Budgeting System is given and then the recent changes made by the Reagan Administration are discussed. Some remarks on analysis and decision-making at the top government levels are given.